Multimodal Treatment With ECT for Identity Integration in a Patient With Dissociative Identity Disorder, Complex Post-traumatic Stress Disorder, and Major Depressive Disorder: A Rare Case Report - Webster, Kyle D.; Michalowski, Susan; Hranilovich, Thomas E. (Frontiers in Psychiatry, 2018)
The legitimacy and etiology of Dissociative Identity Disorder (DID) remains a controversial topic within Psychiatry. The two schools of thought are the Post-Traumatic Model (PTM) and the Socio-Cognitive Model (SCM). This case highlights the validity of PTM in an individual who suffered severe and prolonged physical, psychological, and sexual abuse from 2 years old through adulthood. The reported abuse was corroborated and proven on two separate occasions via medical professionals/rape kit and the police. This resulted in the incarceration of one of her abusers. The only way for the patient to cope with the trauma she suffered was to dissociate, which resulted in the development of four full identity alters. In addition to being diagnosed with DID, the patient has been diagnosed with Major Depressive Disorder (MDD), Post-Traumatic Stress Disorder (PTSD), and chronic suicidality. Unable to manage the suicidal ideations and MDD after nearly 10 years of therapy and psychiatric medications, the patient was referred for Electroconvulsive Therapy (ECT). Upon receiving ECT weekly for 2 years, the patient reported having “lost the others.” As ECT progressed she went from having four alters to no alters and at the time of this report only being able to vaguely hear alter #4. With the integration of these alters she had access to the memories and pain that the alters had protected her from. Prior to losing the alters, her long-term memory was impaired by dissociative processes. Her long-term memory was also impaired because when one of the alters was in control of consciousness only that alter remembered what had happened during that time, unless that alter shared what had happened with one or more of the others. It is unclear if frequent ECT was the catalyst that lead to the integration of her alters however, integration finally began following prolonged ECT. This case highlights the importance of the PTM as an etiological description for DID and the importance of mental health providers further studying and researching the effects of ECT on patients with chronic MDD, PTSD, and suicidal intent, especially if these are comorbid with DID.